2019
DOI: 10.1039/c9sc00028c
|View full text |Cite
|
Sign up to set email alerts
|

A2SrMIVS4 (A = Li, Na; MIV = Ge, Sn) concurrently exhibiting wide bandgaps and good nonlinear optical responses as new potential infrared nonlinear optical materials

Abstract: A series of A2SrMIVS4 compounds concurrently exhibiting wide bandgaps and good NLO responses were proven as promising IR NLO materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 68 publications
4
43
0
Order By: Relevance
“…For Li 2 PbSiS 4 , it can be seen that the lithium orbitals have nearly no involvement in the states near the Fermi energy, E F . This is in agreement with the calculated DOS for Li 2 SrSiS 4 (Yang et al, 2020), Li 2 SrGeS 4 , and Li 2 SrSnS 4 (Wu et al, 2019). On the other hand, when I = Cu or Ag in the I 2 -II-IV-VI 4 compounds, the Cu/Ag orbitals donate significantly to the states at the VB Max .…”
Section: Tablesupporting
confidence: 89%
See 3 more Smart Citations
“…For Li 2 PbSiS 4 , it can be seen that the lithium orbitals have nearly no involvement in the states near the Fermi energy, E F . This is in agreement with the calculated DOS for Li 2 SrSiS 4 (Yang et al, 2020), Li 2 SrGeS 4 , and Li 2 SrSnS 4 (Wu et al, 2019). On the other hand, when I = Cu or Ag in the I 2 -II-IV-VI 4 compounds, the Cu/Ag orbitals donate significantly to the states at the VB Max .…”
Section: Tablesupporting
confidence: 89%
“…attributed to the IV-VI 4 units (Yang et al, 2020;Wu et al, 2017Wu et al, , 2019. We have generally observed that the Pb analogs tend to have narrower bandgaps in most cases where I = Li and Cu (Table 5).…”
Section: Tablementioning
confidence: 81%
See 2 more Smart Citations
“…Recently, by considering the structure merits of the classical NLO materials, aliovalent substitution strategy has been proved to be an effective method to develop the NLO materials with improved properties . For example, many excellent deep‐ultraviolet or infrared (IR) NLO materials including Sr 2 Be 2 B 2 O 7 (SBBO), K 3 Ba 3 Li 2 Al 4 B 6 O 20 F, Li 2 ZnSiS 4 , and Li 2 SrGeS 4 have been structurally designed from the commercialized KBe 2 BO 3 F 2 (KBBF) or AgGaS 2 …”
Section: Figurementioning
confidence: 98%